تأثير أبعاد جودة الخدمة في رضا عملاء المنشآت الفندقية: دراسة ميدانية على عملاء فنادق الخمس نجوم في مدينة دمشق - الراعى، ماهر (جامعة البعث, 2019)
The aim of the research is to define the quality of service and its importance, in addition to identifying the level of customer satisfaction with the quality of the hotel services provided and the impact of the quality of the hotel services such as reliability, response, empathy and safety, in addition to the tangible physical environment in the customer satisfaction. The researcher used the descriptive approach based on reviewing the previous studies and reviewing the latest literature in this field. The analytical method was also used in the statistical analysis method. The questionnaire was distributed to a sample of five star hotel clients in Damascus. And statistical analysis of the questionnaire using the SPSS program to prove the hypothesis of research, the sample size was 232 hotel customers. The research found that there is an impact on the quality of service in the satisfaction of hotel customers. The researcher found that there is a relationship between the quality of services provided and the satisfaction of the customers as these services have a good level of reliability, responsiveness, empathy, safety, In addition to concrete.
هدف البحث إلى التعريف بمفهوم جودة الخدمة وأهميته بالإضافة إلى التعرف على مستوى رضا العملاء عن جودة الخدمات الفندقية المقدمة وأثر أبعاد جودة الخدمة الفندقية كالاعتمادية، الاستجابة، التعاطف، الأمان، بالإضافة إلى البيئة المادية الملموسة في رضا عملاء الفندق. اعتمد الباحث على المنهج الوصفي القائم على مراجعة الدراسات السابقة والاطلاع على أحدث الأدبيات في هذا المجال، كما تم استخدام المنهج التحليلي باستخدام أسلوب التحليل الإحصائي، وذلك بتوزيع استبيان على عينة من عملاء فنادق الخمس نجوم في دمشق، وتحليل الاستبيان إحصائيا باستخدام برنامج SPPS من أجل إثبات فرضيات البحث، وقد بلغ حجم العينة المدروسة 232 من عملاء الفنادق. توصل البحث إلى وجود تأثير لأبعاد جودة الخدمة في رضا عملاء الفنادق، حيث توصل الباحث إلى وجود علاقة بين جودة الخدمات المقدمة والرضا لدى العملاء حيث أن هذه الخدمات تتمتع بمستوى جيد من حيث الاعتمادية، الاستجابة، التعاطف، الأمان، بالإضافة إلى الملموسية.
Keywords: جودة الخدمة -- جودة الخدمة الفندقية -- رضا العملاء -- المنشآت الفندقية -- فنادق الخمس نجوم -- مدينة دمشق